(untitled) (Iranian Journal of Kidney Diseases, 2022)
Introduction. Cilostazol is an antiplatelet agent, that has been recently used as an adjunctive therapy in the management of diabetic foot ulcers. Headache, diarrhea, palpitations, and edema are reported as common side effects. Case Presentation. A 53-year-old woman was admitted to hospital, with decreased urine output and increased serum creatinine level. She had taken Cilostazol for the first time, for only one day, so the diagnosis of acute kidney injury, probably drug-induced acute interstitial nephritis, due to Cilostazol use, was made. Her kidney function did not improve despite Cilostazol discontinuation and therefore, empirical corticosteroid therapy was initiated. Her urine output increased and her serum creatinine level significantly decreased, on the third day of treatment. She was discharged with acceptable kidney function. Follow-up visits showed gradual normalization of serum creatinine in the next 62 days. Conclusion. Based on our case, we may draw the conclusion that, Cilostazol may cause nephrotoxicity at any point after ingestion. DOI: 10.52547/ijkd.6980